Membaca 2 Tawarikh 7:14 dalam Konteks Kebangunan Rohani di Kabupaten Supiori, Papua - Ferra Wanggai; Gernaida Krisna R. Pakpahan (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2024)
This study investigates the potential of intercessory prayer, as outlined in 2 Chronicles 7:14, as a transformative strategy for advancing Supiori Regency, recognized as the "Island of the Gospel." Intercessory prayer, which emphasizes humility, seeking God, and collective repentance, is pivotal in addressing the region's social, economic, and spiritual challenges. With a poverty rate nearing 40%, the integration of spiritual transformation through intercessory prayer with local cultural values—such as respect, unity, and mutual cooperation—serves as a foundation for fostering social harmony and community well-being. Employing a descriptive qualitative approach, this study utilizes theological hermeneutic analysis to assess the implementation of Gospel principles in societal governance and administration. The findings reveal that intercessory prayer functions as a catalyst for restoring spiritual connections with God while simultaneously strengthening social solidarity. Moreover, intercessory prayer provides a framework for local leaders to develop policies grounded in justice and communal welfare. The integration of prayer practices with cultural values presents a model for spiritual and social transformation applicable to other regions, aligning with Supiori's vision of becoming a harmonious, inclusive, and empowered society.